RETRACTION: MANAJEMEN STRATEGIK LEMBAGA PENDIDIKAN ISLAM DALAM MENINGKATKAN MUTU PENDIDIKAN Studi Kasus di Madrasah Aliyah Nahdlatul Ulama Gondang Sragen - Etik Kurniawati (Quality Assurance Institute (LPM) State Islamic University Walisongo Semarang, 2017)
The quality of education in Islamic educational institutions today is encouraged unmediately by the various strategies and approaches. It is underpinned based on a strong desire to build a more dignified education. A strong desire is unfortunately not based on good management so that some Islamic educational institutions should decline. Eventually some Islamic educational institutions today are often considered as an institution that has not been able to manage and produce out put that satisfy customers. The focus of this research is: (1) How is the formulation strategy Islamic educational institutions in improving the quality of education in MA NU Gondang Sragen? (2) How is the implementation strategy of Islamic educational institutions in improving the quality of education in MA NU Gondang Sragen? (3) How is the evaluation strategy of Islamic educational institutions in improving the quality of education in MA NU Gondang Sragen?. In this study, researchers used a qualitative approach with case study design. The data collection conducted by interview, observation and documentation. Data were analyzed by using data reduction techniques, followed by a presentation of data, and drawing conclusions. Results of this research are: (1) Formulation of strategies in MA NU Gondang Sragen done by first formulating the vision and mission of taking into account the internal and external environment, followed by setting goals and targets and continued by the determining strategies. (2) Implementation of the strategy at MA NU Gondang Sragen done by outlining strategies have been formulated in the form of activities. Technical implementation is submitted to the coordinator of activities in coordination with the principal. System monitoring is done by applying an intensive communication and routine control to the coordinator of activities. (3) Evaluation strategies in MA NU Gondang Sragen done through formal and informal meetings. Formal meetings are routinely performed both at the internal level and overall field. By this meeting, then formulated corrective measures forward.